Illustrated Barcodes of Picturebooks: Artistic Peritextual Elements with Pedagogical Applicability. - Fleta, M. Teresa (Children's Literature in Education, 2022)
This study explores the potential of illustrated barcodes of picturebooks in the educational context. The study reviews the modification by artists of conventional and mandatory barcodes into creative barcode placements in picturebooks. By raising awareness of the aesthetic subtleties of barcodes, the paper articulates how these attractive and ironical peritextual elements may have pedagogical applicability. The study brings to the surface these invisible artistic elements to better appreciate their aesthetic potential for read alouds. For exploring the rich diversity of depictions, a corpus of 500 illustrated barcodes was grouped and analyzed into categories with the creators' explanation for the use of these artistic peritextual features. Findings based on quantitative and qualitative content analysis suggest that illustrated barcodes comprise significant information that educators may use during picturebook read aloud sessions. Educators familiar with the hidden information within illustrated barcodes may guide children into exploring these peritextual features and talk about them during interactive storytime.